Synthesis of Cellulose Diethylamino Ammoniumphosphonite and its Thermal Degradation Kinetics - Malhotra, Deepa; Kumar, Krishan; Dahiya, J.B. (Asian Journal of Chemistry, 2010)
Cellulose diethylamino ammoniumphosphonite (CEAP) has been synthesized and characterized. Flame retardancy potential of CEAP was investigated by the kinetics of thermal degradation using differential scanning calorimetery and thermogravimetery in air and He atmosphere. From the resulting data of thermogram curve using Broido method, the activation energy of CEAP (51.3 kJ mol-1) for decomposition process is found lower than that of cellulose (155.3 kJ mol-1) in air. The higher char yield of CEAP (28.3 %) as compared to cellulose (3.1 %) at 700 ºC in air and related observations lead to conclusion that such modification may give rise to novel flame retardant treatment for cellulosic materials.